KAJIAN EFEKTIVITAS PUZZLE GAME AKSARA BALI SEBAGAI MEDIA PENDUKUNG PEMBELAJARAN BAGI ANAK SEKOLAH DASAR DI DENPASAR - Ngurah Adhi Santosa; A.A. Sagung Intan Pradnyanita; Made Arini Hanindharputri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2019)
Literacy is a system of graphical signs or visual symbols of the language that people use to communicate. Balinese script is a mother tongue for Balinese people, which is still used for the benefit of social order and religious ceremonies.For this reason, Balinese script is very important to learn and understand from an early age.But its existence is now increasingly marginalized, along with the times.In its current development, the interest of children to learn Balinese script is decreasing.One of the factors causing a reduction in children's interest in learning Balinese script is a learning system by using conventional media with lectures in class and guided by manuals or student worksheets that contain more text than illustrative illustrations, so that it becomes less interesting and boring. So that learning supporting media is needed, with Balinese Script Puzzle Game that are in accordance with the Balinese Language curriculum for grade 1-3 elementary school children.The purpose of this study was to examine the extent of the effectiveness of the Balinese Script Puzzle Game as a supporter of Balinese script learning and preservation of Balinese script for technology-based grade 1-3 elementary school children.The research method used is qualitative and quantitative methods by going through several stages, among others, beginning with observations by observing the extent to which interest in elementary school children in grades 1-3 on the Balinese Script Puzzle Game,and observe changes that occur after trying to use the Balinese Script Game Puzzle as a supporter of Balinese Script learning. The next stage is doing sampling and measuring the level of effectiveness based on the data obtained and the measurement scale.